Model Inovasi Pengembangan Bisnis Food Corporation “Dear Me Sweety” Dalam Memilih Makanan Penutup yang Rendah Kalori - Raisa Rafifiti Choerunnisa; Budi Setiawan (Akademi Sekretari Manajemen Taruna Bakti, 2022)
Researchers raised a problem that is currently happening a lot among Millennials, namely Diabetes. Indonesia is the fourth largest country with diabetes mellitus in the world, with a population of 21.3 million in 2030. Therefore, an anticipation and innovation of a healthy and low-calorie food product is needed in order to reduce the number of people with diabetes mellitus. The purpose of this research is to produce an innovative new business model so that it can be applied to the community so that it can make it easier for people to make business and also get investors. This study uses the R & D method because the final result of this research will produce food innovation products in the form of low-calorie dessert products. The data presented using descriptive method. The method of data collection is through literature study with secondary data, namely data or information taken from books, journals and the internet. The results of this study indicate that Dear Me Sweety is an innovation that presents a delicious and healthy low-calorie dessert. In addition, to provide information to all Indonesian people so that they can carry out a healthy lifestyle so that they can reduce the estimated prevalence and number of people with diabetes mellitus to be less.